Analisis Strategi Pembangunan Unit Pengolahan Ikan Tuna Di PPS Kutaraja - Firdaus Husen; Achmad Poernomo; Agus Heri Purnomo (Universitas Teuku Umar, 2022)
The Kutaraja PPS manager needs to develop a UPI development strategy at the Kutaraja Ocean Fishery Port by considering internal (strengths and weaknesses) and external factors (opportunities and threats) as well as determining the right strategy in Kutaraja PPS. The study used a qualitative descriptive research method to explain and describe the conditions and situations of PPS Kutaraja. This study aimed to analyze the development strategy of processing units at PPS Kutaraja using SWOT analysis. The results showed that the strength factor score (2.48) was higher than the weakness factor score (1.02) with a difference of 1.46. The opportunity factor score (1.67) was higher than the threat factor score (1.62). Therefore, the strategy needed was an aggressive strategy. In conclusion, the construction of new fish units still could be carried out at the Kutaraja Ocean Fishery Port due to the availability of raw materials that have not been utilized optimally.Keywords: SWOT analysis, Processing Unit Development Location, PPS Kutaraja.